LITERASI BUDAYA DAN KEWARGAAN PADA PEMBELAJARAN ABAD 21 - Ni’matu Sholikhah (Universitas Pahlawan Tuanku Tambusai, 2022)
Literacy has a great influence on the generation of a nation. Every citizen must have literacy skills to become an intelligent citizen. The top priority of a nation is educational progress that suppresses student literacy. One of them is cultural literacy and citizenship. Cultural literacy can be interpreted as the ability to understand and appreciate Indonesian culture as part of national identity. Meanwhile, civic literacy is the ability to understand rights and obligations as citizens. In carrying out cultural and civic literacy, it is guided by six basic principles in supporting cultural and civic literacy: 1. culture as a way of thinking through language and behavior; 2. art as a cultural product; 3. multicultural and participatory citizenship; 4. nationalism; 5. inclusiveness; 6. direct experience. Cultural literacy and citizenship are not only carried out in the classroom, but are also based on school culture. Keywords: cultural literacy, civic literacy, 21st century learning